Modeling of hydraulic fracturing in polymineralic rock with a grain-based DEM coupled with a pore network model. (November 2022) - Li, Mengli; Wu, Jianfa; Li, Junfeng; Zhuang, Li; Wang, Shanyong; Zhang, Fengshou
Highlights: A grain-based DEM coupled with a pore network model is established to investigate the hydraulic fracture growth in polymineralic rock. A new algorithm for the toughness-dominated regime is proposed to simulate SC-CO2 fracturing. The effects of fracturing fluids and inherent microstructures of rock on hydraulic fracture growth at grain-scale are investigated. Abstract: Rock is a typical heterogeneous material composed of inherent microstructures at the grain scale. In this paper, a grain-based discrete element model (DEM) coupled with a pore network model is developed to study the interaction behavior between hydraulic fractures and the inherent microstructures of rocks. The numerical model parameters are calibrated using the experimental results on Pocheon granite, and then the model is validated by the plane strain Khristianovic-Geertsma-de Klerk (KGD) analytical solution. The fracture propagation in polymineralic rock involves many unique phenomena at the grain scale, such as intragranular fractures splitting grains, intergranular fractures along grain boundaries, fluid lag, and rock fragments. Compared with high viscosity fluid, supercritical carbon dioxide (SC-CO2 ) driven fractures tend to separate grain boundaries with low local resistance and propagate less smoothly and continuously, more asymmetrically and tortuously. Furthermore, the uniqueness of microstructures controlled by mineral distribution can lead to large variability in fracture paths, but the fracture properties at the macro-scale have not much difference. As the intergranular bonding strength or average grain size increases, a transition from intergranular fracture-dominated to intragranular fracture-dominated is reported. In addition, it is found that the existence of weak grains can result in more intragranular fractures within weak grains and fewer intergranular fractures associated with weak grains. Rock fragments are likely created as a result of the interaction between hydraulic fractures and weak grains and grain boundaries. Our results show that the low-viscosity fracturing fluid and the strong micro heterogeneity of microstructures are prone to result in complex fracture propagation.